2012
DOI: 10.1099/vir.0.044735-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of capsid modifications by selected peptide ligands on recombinant adeno-associated virus serotype 2-mediated gene transduction

Abstract: Vectors based on adeno-associated virus serotype 2 (AAV2) belong to today's most promising and most frequently used viral vectors in human gene therapy. Like in many other vector systems, the broad but non-specific tropism limits their use for certain cell types or tissues. One approach to screen for transduction-improved vectors is the selection of random peptide libraries displayed directly on the AAV2 capsid. Although the AAV2 library system has been widely applied for the successful selection of improved g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Studies have shown that selecting for capsid modified AAV with improved transduction capacity yields peptides that improve subcellular localization and intracellular processing relative to AAV2. 45 Although the GMN peptide was isolated for endothelial binding and not transduction, it is still possible that it could beneficially modulate restrictive events such as evasion of proteosomal degradation, nuclear trafficking, and capsid uncoating. Furthermore, if the GMN modification does affect these processes, it may provide a partial mechanistic explanation for why AAV-GMN but not AAV2 robustly transduces brain endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that selecting for capsid modified AAV with improved transduction capacity yields peptides that improve subcellular localization and intracellular processing relative to AAV2. 45 Although the GMN peptide was isolated for endothelial binding and not transduction, it is still possible that it could beneficially modulate restrictive events such as evasion of proteosomal degradation, nuclear trafficking, and capsid uncoating. Furthermore, if the GMN modification does affect these processes, it may provide a partial mechanistic explanation for why AAV-GMN but not AAV2 robustly transduces brain endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…At the highest MOI, ~1.4% of AAV2, ~2.5% of AAV2-TRP and ~8.5% of AAV-ShH19 infected cells tested RFP positive by flow cytometry (Figure 1). Use of an MOI of 10,000 for in vitro transduction was in the range reported by others for different glioma cell lines [38,39,53]. Both rAAV2-TRP and rAAV-ShH19 demonstrated higher transduction efficiency for GL261 cells in vitro compared to rAAV2-WT (2- and 6-fold, respectively).…”
Section: Resultsmentioning
confidence: 59%
“…These investigations focus as of yet on the AAV2 capsid position 587 located at the tip of the second highest protrusion [13,[40][41][42][43]. This is maybe caused historically as this position was the first that enabled production of AAV targeting vectors with reasonable titers [44].…”
Section: Rational Design-based Approaches That Alter Aav-host Interacmentioning
confidence: 98%